Doa1 is a MAD adaptor for Cdc48 - Zhang, Ting (J Cell Biol, 2016)
Dislocation of polypeptides from the mitochondrial outer membrane by the p97/Cdc48–Ufd1–Npl4 adenosine triphosphatase complex is essential for mitochondria-associated degradation and Parkin-mediated mitophagy. In this issue, Wu et al. (2016. J. Cell Biol. http://dx.doi.org/10.1083/jcb.201510098) identify Doa1 as a pivotal adaptor that recruits substrates to Cdc48 for processing.